Acetic Acid Assisted Crystallization Strategy for High Efficiency and Long‐Term Stable Perovskite Solar Cell. Issue 5 (23rd January 2020) - Li, Yong; Shi, Junwei; Zheng, Jianghui; Bing, Jueming; Yuan, Jianyu; Cho, Yongyoon; Tang, Shi; Zhang, Meng; Yao, Yin; Lau, Cho Fai Jonathan; Lee, Da Seul; Liao, Chwenhaw; et al.
Abstract: Improving the quality of perovskite poly‐crystalline film is essential for the performance of associated solar cells approaching their theoretical limit efficiency. Pinholes, unwanted defects, and nonperovskite phase can be easily generated during film formation, hampering device performance and stability. Here, a simple method is introduced to prepare perovskite film with excellent optoelectronic property by using acetic acid (Ac) as an antisolvent to control perovskite crystallization. Results from a variety of characterizations suggest that the small amount of Ac not only reduces the perovskite film roughness and residual PbI2 but also generates a passivation effect from the electron‐rich carbonyl group (CO) in Ac. The best devices produce a PCE of 22.0% for Cs0.05 FA0.80 MA0.15 Pb(I0.85 Br0.15 )3 and 23.0% for Cs0.05 FA0.90 MA0.05 Pb(I0.95 Br0.05 )3 on 0.159 cm 2 with negligible hysteresis. This further improves device stability producing a cell that maintained 96% of its initial efficiency after 2400 h storage in ambient environment (with controlled relative humidity (RH) <30%) without any encapsulation. Abstract : Acetic acid (Ac) is used as an antisolvent for preparing perovskite films with excellent optoelectronic properties. Ac is found to not only reduce perovskite film roughness and residual PbI2 but also generate a passivation effect from the electron‐rich carbonyl group. The best 0.159 cm 2 devices produce efficiencies of 22.0% for Cs0.05 FA0.80 MA0.15 Pb(I0.85 Br0.15 )3 and 23.0% for Cs0.05 FA0.90 MA0.05 Pb(I0.95 Br0.05 )3 .